Type 2 diabetes and risk of incident cancers in China: A prospective study among 0.5 million Chinese adults - Pan, X; He, M; Yu, C; Lu, J; Guo, Y; Bian, Z; Yang, L; Chen, Y; Wu, T; Chen, Z; Pan, A; Li, L (Oxford University Press, 2018)
Using data from the China Kadoorie Biobank study, we conducted a prospective investigation on the association between type 2 diabetes mellitus (T2DM) and cancer risk in Chinese adults. A total of 508,892 participants (mean [standard deviation] age: 51.5 [10.7] years) without prior cancer diagnosis at baseline (2004-2008) were included. We documented 17,463 incident cancer cases during follow-up until December 31, 2013. Participants with T2DM had an increased risk of total and certain site-specific cancers, and the hazard ratio (HR) was 1.13 (95% confidence interval [CI]: 1.07, 1.19) for total cancer, 1.51 (1.29, 1.76) for liver cancer, 1.86 (1.43, 2.41) for pancreatic cancer, and 1.21 (1.01, 1.47) for female breast cancer. The associations were largely consistent when doctor-diagnosed and screen-detected T2DM were analyzed separately, except for colorectal cancer (HR: 0.91 [95% CI: 0.73, 1.13] for doctor-diagnosed T2DM, and HR: 1.44 [95% CI: 1.18, 1.77] for screen-detected T2DM). In participants without prior diagnosis of T2DM, higher random blood glucose levels were positively associated with risk of total cancer, liver cancer, and female breast cancer (all P for trend ≤ 0.02). In conclusion, T2DM is associated with an increased risk of new-onset cancer in China, particularly cancers of the liver, pancreas, and female breast.